Kinetics and mechanism of the cleavage of Phthalic Anhydride in Glacial Acetic Acid Solvent containing Aniline - Ariffin, Azhar; Khan, M.N.; Damit, E.F. (2008)
Apparent second-order rate constants (k(n)(app)) for the nucleophilic reaction of aniline (Ani) with phthalic anhydride (PAn) vary from 6.30 to 7.56 M(-1) s(-1) with the increase of temperature from 30 to 50 degrees C in pure glacial acetic acid (AcOH). However, the values of pseudo-first-order rate constants (k(s)) for the acetolysis of PAn in pure AcOH increase from 16.5 x 10(-4) to 10.7 x 10(-3) s-1 with the increase of temperature from 30 to 50 degrees C. The values of k(n)(app) and k(s) vary from 5.84 to 7.56 M(-1) s(-1) and from 35.1 x 10(-4) to 12.4 x 10(-4) s(-1), respectively, with the increase of CH(3)CN content from 1% to 80% v/v in mixed AcOH solvents at 35 degrees C. The plot of k(s) versus CH(3)CN content shows a minimum (with 10(4) k(s) = 4.40 s(-1)) at 50% v/v CH(3)CN. Similarly, the variations of k(n)(app) and k(s) with the increasing content of tetrahydrofuran (THF) in mixed AcOH solvent reveal respective a maximum (with k(n)(app) = 17.5-15.6 M(-1) s(-1)) at 40-60% v/v THF and a minimum (with k(s) = similar to 0-1.2 x 10(-4) s (-1)) at 60-70% v/v THF. The respective values of Delta H* and Delta S * are 15.3 +/- 1.2 kcal mol(-1) and -20.1 +/- 3.8 cal K(-1) mol(-1) for k(s) and 1.1 +/- 0.5 kcal mol(-1) and -51.2 +/- 1.7 cal K(-1) mol(-1) for k(n)(app), while the values of k(n) (= k(n)(app)/f(b) with f(b) representing the fraction of free aniline base) are almost independent of temperature within the range 30-50 degrees C. A spectrophotometric approach has been described to determine f(b) in AcOH as well as mixed AcOH-CH(3)CN and AcOH-THF solvents. Thus, the observed data, obtained under different reaction conditions. have been explained quantitatively. An optimum reaction condition, within the domain of present reaction conditions, has been suggested for the maximum yield of the desired product, N-phenylphthalamic acid.